Add them all up to get the answer
Answer:
ok im not him but can you give me brainliest
Step-by-step explanation:
Answer:
-1/2, 7
Step-by-step explanation:
Given the expression
(x -7)(-4x -2)=0
This means that;
x - 7 = 0 and -4x - 2 = 0
x = 0+7 snd -4x = 2
x = 7 and x = -2/4
x = 7 and -1/2
Hence the solution from least to greatest is -1/2, 7
Answer:
B
Step-by-step explanation:
y³=64
![y=(64)^{\frac{1}{3} } =\sqrt[3]{64}](https://tex.z-dn.net/?f=y%3D%2864%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%3D%5Csqrt%5B3%5D%7B64%7D%20)
H=A/0.5b isolate h
h=2A/b Make all terms integers (optional)